Neuroprotective Approaches for Brain Injury After Cardiac Arrest: Current Trends and Prospective Avenues - Subash Marasini; Xiaofeng Jia (Journal of Stroke, 2024)
With the implementation of improved bystander cardiopulmonary resuscitation techniques and public-access defibrillation, survival after out-of-hospital cardiac arrest (OHCA) has increased significantly over the years. Nevertheless, OHCA survivors have residual anoxia/reperfusion brain damage and associated neurological impairment resulting in poor quality of life. Extracorporeal membrane oxygenation or targeted temperature management has proven effective in improving post-cardiac arrest (CA) neurological outcomes, yet considering the substantial healthcare costs and resources involved, there is an urgent need for alternative treatment strategies that are crucial to alleviate brain injury and promote recovery of neurological function after CA. In this review, we searched PubMed for the latest preclinical or clinical studies (2016–2023) utilizing gas-mediated, pharmacological, or stem cell-based neuroprotective approaches after CA. Preclinical studies utilizing various gases (nitric oxide, hydrogen, hydrogen sulfide, carbon monoxide, argon, and xenon), pharmacological agents targeting specific CA-related pathophysiology, and stem cells have shown promising results in rodent and porcine models of CA. Although inhaled gases and several pharmacological agents have entered clinical trials, most have failed to demonstrate therapeutic effects in CA patients. To date, stem cell therapies have not been reported in clinical trials for CA. A relatively small number of preclinical stem-cell studies with subtle therapeutic benefits and unelucidated mechanistic explanations warrant the need for further preclinical studies including the improvement of their therapeutic potential. The current state of the field is discussed and the exciting potential of stem-cell therapy to abate neurological dysfunction following CA is highlighted.